The Edinburgh history of reading : subversive readers - Rose, Jonathan, 1952- (Edinburgh : Edinburgh University Press, 2020)
Subversive Readers explores the strategies used by readers to question authority, challenge convention, resist oppression, assert their independence and imagine a better world. This kind of insurgent reading may be found everywhere: in revolutionary France and Nazi Germany, in Eastern Europe under Communism and in Australian and Iranian prisons, among eighteenth-century women reading history and nineteenth-century men reading erotica, among postcolonial Africans, the blind, and pioneering transgender activists.
History, politics and the separate spheres: women's reading in eighteenth-century Britain and America / Mark Towsey -- Reading in Australian prisons: an exploration of motivation / Mary Carroll and Jane Garner -- Hawking terror: reading the French Revolutionary Press / Valerae Hurley -- Hellfire and cannibals: eighteenth- and nineteenth-century erotic reading groups and their manuscripts / Brian M. Watson -- The 'tactile ba[b]bl under which the blind have hitherto groaned': dots, lines and literacy for the blind in nineteenth-century North America / Joanna L. Pearce -- British cultures of reading and literary appreciation in nineteenth-century Singapore / Porsche Fermanis -- Moral readership and political apprenticeship: commentaries on English education in India, 1875-1930 / Pramod K. Nayar -- The 'pleasure and profit' of reading: adolescents and juvenile popular fiction in the early twentieth century / Trudi Abel -- Trans culture and the circulation of ideas / Lisa Z. Sigel -- Reading history, history reading in modern Iranian literature: prison writing as national allegory or a world literary genre? / Alireza Fakhrkonandeh -- Beyond Mein Kampf: bestsellers, writers, readers and the politics of literature in Nazi Germany / Christian Adam -- Reading spaces in Japanese-occupied Indonesia: the project to create and translate a Japanese-language library / Atsuhiko Wada, translated by Edward Mack -- Just send Zhivago: reading over, under and through the iron curtain / Jessica Brandt -- African readers as world readers: UNESCO, worldreader and the perception of reading / Ruth Bush -- The Kindle era: DIY publishing and African-American readers / Kinohi Nishikawa -- 'I loved the stories -- they weren't boring': narrative gaps, the 'disnarrated' and the significance of style in prison reading groups / Patricia Canning
Includes bibliographical references and indexes
Print version record
JSTOR
Keywords: Books and reading -- History; Books and reading -- England -- History -- 18th century; Books and reading -- England -- History -- 19th century; Publishers and publishing -- England -- History -- 18th century; Publishers and publishing -- England -- History -- 19th century; Popular culture -- England -- History; England -- Intellectual life -- History; Authors and readers -- England; Livres et lecture -- Histoire; Livres et lecture -- Angleterre -- Histoire -- 18e siècle.; Livres et lecture -- Angleterre -- Histoire -- 19e siècle.; Culture populaire -- Angleterre -- Histoire; Angleterre -- Vie intellectuelle -- Histoire; Écrivains et lecteurs -- Angleterre; Angleterre -- Vie intellectuelle; LITERARY CRITICISM -- General; Books and reading; Authors and readers; Intellectual life; Popular culture; Publishers and publishing; England; 1700-1899; History